A Key Role in Catalysis and Enzyme Thermostability of a Conserved Helix H5 Motif of Human Glutathione Transferase A1-1 - Chronopoulou Evangelia G; Mutabdzija Lana; Poudel Nirmal; Papageorgiou Anastassios C; Labrou Nikolaos E (MDPI, 2025)
Glutathione transferases (GSTs) are promiscuous enzymes whose main function is the detoxification of electrophilic compounds. These enzymes are characterized by structural modularity that underpins their exploitation as dynamic scaffolds for engineering enzyme variants, with customized catalytic and structural properties. In the present work, multiple sequence alignment of the alpha class GSTs allowed the identification of three conserved residues (E137, K141, and S142) at alpha-helix 5 (H5). A motif-directed redesign of the human glutathione transferase A1-1 (hGSTA1-1) was performed through site-directed mutagenesis at these sites, creating two single- and two double-point mutants (E137H, K141H, K141H/S142H, and E137H/K141H). The results showed that all the enzyme variants displayed enhanced catalytic activity compared to the wild-type enzyme hGSTA1-1, while the double mutant hGSTA1-K141H/S142H also showed improved thermal stability. X-ray crystallographic analysis revealed the molecular basis of the effects of double mutations on enzyme stability and catalysis. The biochemical and structural analysis presented here will contribute to a deeper understanding of the structure and function of alpha class GSTs.